Textbook ranking and an assessment method and system: a case study using surveying textbooks. Issue 5 (26th November 2020) - Kuo, Chien-Min; Chen, Kuan-Yu; Lin, Yi-Ching
Abstract : Purpose: Teachers, students, librarians, scholars and domain experts often spend a lot of time and effort to select good and suitable textbooks. This study aims to propose and construct a computer-aided bibliometric system to rate textbooks. Through the software system designed here, the quality of every textbook can be easily and quickly known. This system will benefit both scholars and librarians. Design/methodology/approach: Four methods were used to evaluate textbooks in this study, including: questionnaire recommendation analysis, dissertation citation analysis, library circulation analysis and bibliography analysis. The system architecture includes three subsystems: the textbook indexing and searching subsystem, the statistics added-value analysis subsystem and the citation report inquiry subsystem. An example demonstrates the usability and validity of the proposed method and system. The example uses surveying textbooks. The following percentages were used in the correlation calculation: textbook citation percentage (TCP), textbook library circulation percentage (TLP) and textbook recommend percentage (TRP). Findings: There are three textbook assessment methods applied in this study, including: dissertation citation, library circulation and questionnaire recommendation. Dissertation citations for textbooks have a high correlation value with library circulation. The frequency correlation calculation was 0.7, while the TCP, TLP and TRP correlation calculation was 0.84. Therefore, the dissertation citation method can be accepted to evaluate textbooks effectively. Originality/value: To the best of the authors' knowledge, this is the first work related to evaluating surveying textbooks using a computer-aided bibliometrics system that can deal with large amounts of data and generate results quickly. This can be applied to other fields as well.